Implementasi Laporan Keuangan Menggunakan Aplikasi Accurate pada Sekolah Luar Biasa Perguruan Al-Azhar - Toyibah Nur Nst; Zakia Fadila (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
In every life and process of human development there is always something called calculating numbers. Calculations will often involve accounting knowledge. Accounting science is a pure science that humans use to solve their financial problems to become more organized and structured. Likewise with trading companies or service companies that use helper applications to complete their financial processes to make them more efficient and stable. Such as the Al-Azhar School for Special Education which is used as a forum for completing the preparation of financial administration calculations using accounting data which is applied to the method of completion using Accurate software. The accounting data used are in the form of general journals, ledgers, balance sheets and income statements. This calculation is carried out in a thorough and good way using accurate software based on the correct guide within a certain time to complete the financial administration calculation process until it is finished.